INCREASING STUDENT ENGAGEMENT IN SCHOOL HISTORY LESSONS AND UTILIZING LOCAL SOURCES ON THE HISTORY OF THE SECOND WORLD WAR: EXPERIENCE AND RESEARCH (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores strategies for enhancing student engagement in history lessons by incorporating local sources related to World War II. It emphasizes the importance of instilling historical awareness and national identity among students, a task that has become especially relevant in the post-independence period. The study underscores the value of creative teaching approaches that foster historical thinking and written expression, including the use of student projects, local historical narratives, and map-based research. Drawing on practical experiences from Surxondaryo region, the article integrates archival materials and accounts of local war veterans to enrich the teaching content. It also examines the responsibilities of teachers in organizing history lessons using modern pedagogical and information-communication technologies. Overall, the article provides a methodological foundation for renewing history education and developing students' historical consciousness through innovative practices.